Pompeian Plasters Database - Freccero, Agneta (Swedish Institute in Rome, 2012)
The study presented in this database concerns plasters used for wall decorations in Pompeii. Earlier experiences in the field showed that plasters compositions change over time. The hypothesis for the study was that there is a connection between the typology and the relative chronology in which the plasters appear on the walls, and that these factors are related not only in single houses or quarters but over the site. The variations were assumed to be related to technology, craftsmanship and fashion. Focus has been set on materials and styles. The database has three sections: Houses, Samples and Types. The types are sorted according to the system of types which is 0 (Zero), which contains the earliest plasters identified, the chronologically namned A-H and the additional X, a group that contains other kinds of materials, such as cocciopesto, modern restoration materials, or waterproof plaster, just to mention some.

Purpose:

The main objective of this project is to study lime plasters used for wall decoration and, if possible, to find a clear relation between typology and stratigraphy.

Studien som presenteras i databasen avser dekorationsputser som används vid väggmålning i Pompeji. Tidigare erfarenheter inom området har visat att putsernas sammansättning förändras över tid. Studien utgick från hypotesen att det finns ett samband mellan putsernas typologi och relativa kronologi, i betydelsen i vilken ordning de uppträder på väggarna, och att dessa faktorer är relaterade inte bara i enskilda hus eller kvarter utan i hela staden. Databasen har tre delar; Houses (Hus), Samples (Prover) och och Types (Typer). Typerna sorteras enligt följande; 0 (Noll), vilken innehåller de äldsta identifierade putserna, de kronologiskt löpande A-H och tilläggstypen X, en grupp som innehåller andra typer av material, som cocciopesto, moderna restaureringsmaterial och vattentät puts, för att nämna några.

Syfte:

Projektets huvudsyfte är att undersöka kalkputs som använts för väggdekoration och att, om möjligt, hitta en tydlig relation mellan typologi och stratigrafi.
Databas över pompejanska putser
Keywords: mural; muralmåleri; fresco; fresk; HISTORY; HISTORIA; Analytical Chemistry; Analytisk kemi; Inorganic Chemistry; Oorganisk kemi; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Classical Archaeology and Ancient History; Antikvetenskap